If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2x = 3x + -18 Reorder the terms: 7 + -2x = -18 + 3x Solving 7 + -2x = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + -2x + -3x = -18 + 3x + -3x Combine like terms: -2x + -3x = -5x 7 + -5x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + -5x = -18 + 0 7 + -5x = -18 Add '-7' to each side of the equation. 7 + -7 + -5x = -18 + -7 Combine like terms: 7 + -7 = 0 0 + -5x = -18 + -7 -5x = -18 + -7 Combine like terms: -18 + -7 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| (3x-1)y=6y-10(3x-1)^1/3 | | 3v+9=63 | | X^2-2=38 | | -6x=10-6x | | xyz=4x+2y-5z | | 12x+x^2=180 | | 2y+-(14)x= | | 7x+6+4x/3=-11 | | 2y-(6y+1)= | | 2y^2=3(y+3) | | (-14)+(4)= | | 25=log(x) | | 4(-7)(-7)(-7)+2(3)= | | 6=2x-14 | | 14x+31y=-6 | | 8y-40=0 | | 0=2w+10 | | 4x+2c= | | 6x+6-9(x+1)=3x+2 | | 6x-20=-14x+5(4x-4) | | Sinx=0.07 | | 0.8x+0.3(20-x)-0.5x=19 | | V=4/3πr3 | | 5(6z-1)-4(z+4)=12(z+1) | | 1/8(4/3)-1/6 | | x^2-19=18x | | 9/4x-5=4 | | 3x+9-7(x+1)=5x+7 | | 2x-6x+4x-7x= | | 6w+3-10=7w-8 | | 3x+4t=m-7 | | 7-9[3-(9y-8)]= |